Identification, Whole-Genome Sequencing and Analysis of Vibrio alginolyticus S10, a Strain Producing Alginate Lyase - LIU Fang, SHU Zhiqiang, WANG Gongming, JING Yuexin, ZHAO Yunping, XU Yingjiang, JIAO Chunna, ZHANG Jian (Shipin Kexue)
Strain S10, isolated from the intestine of Apostichopus japonicus, is able to produce alginate lyase at a high yield. In order to scrutinize its genome sequence and to explore gene resources related to alginate lyase, strain S10 was identified through morphological observation and 16S rRNA sequence analysis. Then, its whole genome was sequenced using Illumina second-generation sequencing technology and PacBio, the third-generation high-throughput sequencing platform. The sequencing data were used for genome assembly, gene prediction, and gene function annotation. In addition, based on the annotation results, bioinformatics analysis and structure prediction were performed on three sets of putative alginate lyase gene sequences in strain S10. The results showed that strain S10 was identified as Vibrio alginolyticus, with a total genome length of 5 397 046 bp and a GC content of 44.59%. The genome was composed of two chromosomes and one plasmid. A total of 4 936 protein-coding genes, 127 tRNA genes and 37 rRNA genes were predicted. Totally 4 039, 3 163, 3 104 and 96 functional genes were annotated in the Clusters of Orthologous Groups (COG), Gene Ontology (GO), Kyoto Encyclopedia of Genes and Genomes (KEGG) and Carbohydrate-Active EnZymes (CAZy) databases, respectively. In addition, three groups of potential alginate lyase genes, alg4755, alg4756 and alg4760, were found in strain S10. Bioinformatics analysis showed that alginate lyases Alg4755, Alg4756 and Alg4760 all belonged to the polysaccharide lyase family 7 (PL7) and had three highly conserved motifs of the PL7 family, R*E*R, Q(I/V)H and Y*KAG*Y*Q. In summary, the sequencing and analysis of the whole genome of S10 strain is of great significance for understanding the mechanism of efficient enzyme production by this strain and for exploring new alginate lyases, and also provides a theoretical basis for follow-up research on enzyme expression and industrial application.